A convenient catalytic asymmetric conjugate addition reaction to enones using alkylzirconium reagents - Maksymowicz, R; Sidera, M; Roth, P; Fletcher, S (2013)
Alkylzirconium reagents undergo highly enantioselective copper-catalysed 1,4-addition reaction to cyclic enones. These reactions use alkylmetal species generated in situ from alkenes and the Schwartz reagent, and do not require premade organometallic reagents. The reactions have been performed on practical synthetic scales (2.5 mmol) and a scale-up to 10 mmol is demonstrated. The reactions proceed at room temperature, in a variety of solvents, and tolerate many functional groups.© Georg Thieme Verlag Stuttgart New York.